Pengaruh Sistem Pencatatan Akuntansi, Pemahaman Akuntansi, dan Kesiapan Pelaku UMKM terhadap Implementasi SAK EMKM pada UMKM Songket Koto Gadang Kabupaten Agam - Rizka Fadhilah; Immu Puteri Sari; Rina Widyanti; Fitri Yulianis (Jurnal Ilmu Sosial, Ekonomi dan Pendidikan, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in Indonesia's economic development; however, the quality of financial reporting remains a major challenge, particularly in implementing the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). Limited accounting knowledge, inadequate accounting recording systems, and organizational readiness have constrained the adoption of standardized financial reporting among MSMEs. This study aims to examine the influence of accounting recording systems, accounting understanding, and MSME readiness on the implementation of SAK EMKM among Songket Koto Gadang MSMEs in Agam Regency, West Sumatra. A quantitative explanatory survey design was employed involving 100 MSME owners selected through purposive sampling. Data were collected using structured questionnaires and analyzed using multiple linear regression with IBM SPSS Statistics 26. The findings reveal that accounting recording systems, accounting understanding, and MSME readiness simultaneously have a significant effect on the implementation of SAK EMKM. Partially, MSME readiness demonstrates a positive and significant influence, whereas accounting recording systems and accounting understanding exhibit significant but negative relationships with SAK EMKM implementation, indicating that the existence of accounting practices and knowledge alone does not necessarily ensure effective implementation without adequate organizational readiness. The model explains 27.2% of the variation in SAK EMKM implementation. These findings highlight the importance of strengthening accounting competence, organizational readiness, and continuous assistance to improve the quality of financial reporting among culturally based creative MSMEs.